The Pattern of the Relationship between Ethical Philosophies and Information Technology with the Ethical Behavior of Auditors: An Actors Network Theory (ANT) App - Hossein Rajabdorri; Hamidreza Vakilifard; Hojatolah Salari; Ali Amiri (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Ethics is a fundamental issue in the accounting and auditing profession, and the application of IT-related approaches to the financial sciences is undeniable; therefore, the purpose of this study is to prepare a model and systematize the relationship between ethical philosophies and information technology with the moral behaviour of auditors using the ANT.Methodology: The present study is applied in terms of using the findings and qualitative in terms of the research method. It also has a developmental orientation concerning increasing knowledge and presenting a new model. The research population includes studies related to the subject with the same sample. In this regard, no sampling was done, and the sample and the population were considered the same. Then, the final model is prepared with the meta-synthesis of the sample components using the ANT approach. Finally, the importance of the model's components was confirmed by interviewing 5 experts.Findings: Results showed that human and technical actors influence auditors' ethical behaviour. Human actors generally include moral theories, and technical actors typically include information technology. Ethical theories (human actors) are also divided into two general parts: action-based theories and virtue-based theories (virtuosity). Action-based theories also include duty-based (duty-oriented), outcome-based (utilitarianism and otherism), divine-based (benevolence), and justice-based (justice-oriented). Information technology (technical actors) also includes the integrated theory of acceptance and use of advanced technology (motivation, hope for effort, and social impact). The study's overall findings showed that the components of technical and human actors have a positive and significant effect on the development of ethical behaviour in auditors.Originality/Value: Considering the importance of systematizing ethical behaviour and preparing models appropriate to the country's environment, the findings of this study, with strong theoretical and practical support, can help to understand better and accelerate the implementation of auditors' ethical behaviour and human and technical actors and shows the influential role of each one clearly.